Development of a Hybrid Edge-Cloud Integrated Multi-Sensors Monitoring System Dashboard - Eu, Ivan Sik Wei; Azlina Bahari; Law, Brian Jia Ching; Aimi Syamimi Ab Ghafar (Progress in Engineering Application and Technology, 2026)
This thesis entails the development of a hybrid edge-cloud integrated multi-sensor monitoring dashboard, designed to addressed limitation in traditional environment monitoring through the utilization of IoT-enabled real-time data collection and visualization through an interactive dashboard. The system integrates both edge-based sensor nodes with cloud communication protocol and local data processing, creating a scalable monitoring framework for various environmental applications. Utilizing sensors such as PT1000 temperature sensor, pH and TDS sensors from DFRobot was used to demonstrate the feasibility of data transmission from the sensor node all the way to the dashboard. The system is equipped with a Telegram alert as the main way to detect the connectivity of the sensor nodes. Due to the usage of a dashboard, a System Usability Scale (SUS) was utilized and a score of 56.25 was obtained, which indicates the need for further improvement on the dashboard until it reaches an industry standard.